2016
DOI: 10.1155/2016/2185323
|View full text |Cite
|
Sign up to set email alerts
|

Expression Marker-Based Strategy to Improve Beef Quality

Abstract: For beef cattle research, a main objective is to control concomitantly the development of muscles and the qualities of beef cuts. Beef quality is a complex phenotype that is only detectable after slaughter and is highly variable. The beef industry is in need of tools to estimate beef quality of live cattle or online in abattoirs, with specific attention towards sensory attributes (tenderness, juiciness, flavour, and colour). Identification of relevant genetic and genomic markers is ongoing, especially for tend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 42 publications
3
13
0
4
Order By: Relevance
“…This is in line with a prior study, that observed lower proportion of fast twitch oxidative glycolytic fibers and higher of slow twitch oxidative fibers in the Longissimus dorsi muscle of crossbred Angus×Nellore compared to Nellore cattle [27]. In addition, Angus is considered to have a higher proportion of oxidative muscle fibers [28]. Muscle fiber type has been associated with meat quality [29].…”
Section: Resultssupporting
confidence: 89%
“…This is in line with a prior study, that observed lower proportion of fast twitch oxidative glycolytic fibers and higher of slow twitch oxidative fibers in the Longissimus dorsi muscle of crossbred Angus×Nellore compared to Nellore cattle [27]. In addition, Angus is considered to have a higher proportion of oxidative muscle fibers [28]. Muscle fiber type has been associated with meat quality [29].…”
Section: Resultssupporting
confidence: 89%
“…Similarly, selection of animals that carry biomarkers in their genomes that will make them improve their meat production and marbling efficiency is the general goal of researchers passionate about beef production. Currently, identification of relevant genetic and genomic markers is ongoing, especially for tenderness-a top priority quality attribute [84].…”
Section: Gene Regulation In Beef Cattle 31 Mutationsmentioning
confidence: 99%
“…Although caspases are the main effectors of apoptosis, their importance in meat tenderisation process is still debated (Sacc a et al 2015a). For their physiological role as chaperones, anti-apoptotic and anti-oxidative factors, heat shock proteins are involved in the transformation of muscle to meat (Cassar-Malek and Picard 2016). Among these, alphaB-cristallyn and heat shock protein 27 (Hsp27) have been shown to be involved in myofibrillar proteins protection (Guillemin et al 2011;Lomiwes et al 2014) and Hsp27 was reported as related to tenderness (Bernard et al 2007;Sacc a et al 2015a).…”
Section: Introductionmentioning
confidence: 99%